From Passive to Active: The Paradigm Shift of Straw Collection - Wang, Qiang; Yang, Yueling (Frontiers in Ecology and Evolution, 2022)
This paper takes the centralized biogas production project in the energy utilization of straw as a hypothetical item in investigation to discuss the straw collection mode based on the wishes of farmers. Through surveys of farmers in Shandong and Hebei provinces, under the current straw collection price, we found that 85% of farmers have the willingness to actively collect and transport straw, and the longest distance for active transportation is 3.22 km. The willingness of farmers to actively transport is not only affected by personal characteristics, family characteristics, and current energy consumption habits, but also the characteristics of behavioral intervention variables such as knowledge, attitude, and practice of environmental protection also significantly affect the distance of farmers' active transportation. The behavioral intervention variables of these non-economic factors can be interfered and improved through multiple conventional propaganda tools. Therefore, it is necessary to establish a collection and storage point construction model based on the willingness of farmers to realize the transformation of the straw collection model from passive to active. This method also has an important reference value for most straw energy utilization projects. It will have an important impact on the planning, design, and operation of the project.